2013
DOI: 10.1016/j.watres.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of humic acid fouling on membrane performance and transport of pharmaceutically active compounds in forward osmosis

Abstract: The impact of humic acid fouling on the membrane transport of two pharmaceutically active compounds (PhACs) -namely carbamazepine and sulfamethoxazole -in forward osmosis (FO) was investigated. Deposition of humic acid onto the membrane surface was promoted by the complexation with calcium ions in the feed solution and the increase in ionic strength at the membrane surface due to the reverse transport of NaCl draw solute. The increase in the humic acid deposition on the membrane surface led to a substantial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 40 publications
3
62
0
1
Order By: Relevance
“…We surmise that foulant deposition facilitated the formation of a thin fouling layer which reduced reverse solute diffusion. Similar reduction in reverse solute transport was reported in our previous study where humic acid fouling was examined using NaCl draw solution [43].…”
Section: Water Production By Osmotic Dilution For Greenwall Irrigationsupporting
confidence: 84%
“…We surmise that foulant deposition facilitated the formation of a thin fouling layer which reduced reverse solute diffusion. Similar reduction in reverse solute transport was reported in our previous study where humic acid fouling was examined using NaCl draw solution [43].…”
Section: Water Production By Osmotic Dilution For Greenwall Irrigationsupporting
confidence: 84%
“…For instance, X. Jin et al [18] investigated the rejection of pharmaceuticals by FO membranes and found that thin film composite (TFC) polyamide based FO membranes exhibited excellent performance with high water flux and great rejection of pharmaceutical (>94%). Xie and his co-workers [19,20] applied FO to treat the wastewater containing pharmaceutically active compounds and found that humic acid fouling decreased water flux, but enhanced solute rejection. R.V.…”
Section: Introductionmentioning
confidence: 99%
“…Since the active layer of the membrane is characterized by selective ionic penetrability along the flow the transfer of dissolved components J c will take place counter to this flow. As is known, the process of forward osmosis always takes place against the background of internal and external concentration polarization (CP) [17][18][19][20]. External CP appears at the membrane-solution interface.…”
Section: Resultsmentioning
confidence: 99%